Fatty acids in the blubber of minke whales (Balaenoptera acutorostrata) -stratification and relation to diets - Gade-Sørensen, Lars Aage (Universitetet i Tromsø, 2011)
The fatty acid (FA) composition of 37 minke whales (Balaenoptera acutorostrata) from 4 different areas, Spitsbergen, Bjørnøya, Vesterålen and the North Sea was determined. Stratification between inner, middle and outer blubber was present. Most saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) with 20 and 22 carbon atoms had a higher relative amount in the inner blubber while short-chain MUFAs with 14, 16, 17 and 18 carbon atoms had a higher amount in the outer blubber. Whales from the different areas had a different fatty acid composition in inner blubber layer, but a more similar FA composition in outer blubber layer. The inner blubber layer were found different from all potential prey species, even though prey species from expected and observed diets were found with most similar fatty acid composition as the inner blubber layer. Fatty Acid Trophic Markers (FATMs) indicating the copepod Calanus sp. based food-webs, were found in high relative numbers with all whale samples from all areas, FATMS indicating diatoms were found with Spitsbergen/Bjørnøya samples, and FATMs indicating dinoflagellates were found with samples from Vesterålen and the North Sea. FA profiles have the potential in bio monitoring minke whale diet, but more study of the influence of metabolism in FA incorporation of blubber are needed.